Level of Female Students’ Conceptual understanding of and Hybridisation: A Mixed Method Study using a Two-Tier Diagnostic Test (London Journal of Research In Humanities and Social Sciences, 2025)
Female students are underrepresented in science subjects, including chemistry. In Ghana, the West African Examination Council noted that male students outperform females, particularly in atomic orbitals and hybridisation. We examined female chemistry students' understanding of these concepts, considering school types, using an embedded mixed methods design. A total of 304 students, selected through multistage sampling, took a two-tier Atomic Orbitals and Hybridisation Diagnostic Test. Means, standard deviations, frequencies, and percentages were used to analyse the quantitative data on students' conceptual understanding of atomic orbitals and hybridisation. The Mann-Whitney U test compared the mean understanding between female students from single- and mixed-sex schools. Inductive thematic analysis was applied to the qualitative data, supporting the quantitative findings. Female students from single-sex schools exhibited a higher level of conceptual understanding than those from mixed-sex schools, although both groups showed partial understanding. Consequently, it is recommended that the Ministry of Education and Ghana Education Service should provide support services for female students in mixed-sex schools to enhance their learning of chemistry concepts.
Keywords: Faith and Work; Prosperity Gospel; Cost of Discipleship; Poverty Reduction; Religious Laziness; Ghanaian Christianity; campus media; narrative analysis method; Pro-Palestine Protest Movements; The Columbia Daily Spectator; Church.; Church History; African Church History; African Theology; misconceptions; female students; conceptual understanding.; SDG 5